L’image de « la Maghrébine » dans le cinéma français (1970-2007) - Tiphaine Manac’h (Genre & Histoire)
From 1970 to 2007, one hundred and thirty-four French feature films depict a female character from North Africa whether this origin is supposed or clearly specified. The example of three of those films, made in specific production settings and released in specific socio-political contexts, show that the picture of the North African woman – even if more and more significant – is still distorted.